Heat Shock Protein 70 (HSP 70) Level in Threatened Abortion - Utomo, Bram M; Suparman, Eddy; Mamengko, Linda M (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To determine the level of Heat Shock Protein 70 (HSP 70) in threatened abortion compared with normal pregnancy. Method: This was a cross-sectional analytic study design conducted to examine the HSP 70 level on 25 subjects of pregnant women with